2010
DOI: 10.1056/nejmc1004719
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Treatment in Hepatic Encephalopathy

Abstract: Hepatic encephalopathy is a challenging complication in patients with advanced liver disease. It can be defined as a neuropsychiatric syndrome caused by portosystemic venous shunting, ranging from minimal to overt hepatic encephalopathy or coma. Its pathophysiology is still unclear, although increased levels of ammonia play a key role. Diagnosis of hepatic encephalopathy is currently based on specific tests evaluating the neuropsychiatric state of patients and their quality of life; the severity of hepatic enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…This study also showed that the rate of adverse effects with longterm use of rifaximin is low which appeared to be similar to previously reported adverse effects of rifaximin in other studies, 23,26,27 although more than 50% of patients in these studies were cirrhotic because of alcohol abuse.…”
Section: Ta B L Esupporting
confidence: 90%
See 1 more Smart Citation
“…This study also showed that the rate of adverse effects with longterm use of rifaximin is low which appeared to be similar to previously reported adverse effects of rifaximin in other studies, 23,26,27 although more than 50% of patients in these studies were cirrhotic because of alcohol abuse.…”
Section: Ta B L Esupporting
confidence: 90%
“…Although a growing number of studies have proved the efficacy of rifaximin in HE treatment in hepatic patients, 19,23,24,25,26,27,28,29 these studies enrolled patients mainly with alcohol-related cirrhosis and none of them addresses those with HCV-related cirrhosis.…”
mentioning
confidence: 99%
“… Rifaximin is the most used antibiotic in HE because it shows the best efficacy and safety profile, acting on the functionality of the microbiota. It is highly effective in secondary prevention, showing that when added to non-absorbable disaccharides, it prevents a third episode of encephalopathy (hazard ratio = 0.42; 95% confidence interval 0.28–0.64) [ 56 , 57 ]. The combination of lactulose plus rifaximin was more effective than lactulose alone to treat episodic overt HE and reduce mortality due to a reduction in sepsis-related deaths in a trial [ 57 ].…”
Section: Hepatic Encephalopathymentioning
confidence: 99%